Suicidality at the intersection of sex, sexual orientation, and gender expression among secondary school students in Hong Kong: a population-based studyResearch in context - Zixu Li; Paul Siu Fai Yip (The Lancet Regional Health. Western Pacific)
Summary: Background: Previous suicide research has seldom examined the collective impact of multiple social identities/positions, and suicidality among sexual and gender minority adolescents remains understudied in Chinese contexts. Using intersectionality as both a theoretical and analytical framework, we investigate the combined effects of sex, gender expression, and sexual orientation on suicidal ideation and suicide attempts among secondary school students in Hong Kong. Methods: Data from 8023 adolescents (mean age = 14.76, SD = 1.66; 44.56% girls) who participated in the 2021 wave of the Youth Sexuality Study (YSS) were included in analysis. Multilevel analysis of individual heterogeneity and discriminatory accuracy (MAIHDA) estimated the prevalence of suicidal ideation and suicide attempts for adolescents across various combinations of social identities/positions (i.e., sex x gender expression x sexual orientation), assessed the extent to which these identities/positions accounted for the total variance in suicide behaviors, and examined the interactive intersectional effects (i.e., two-way or higher–level interactions) between the identities/positions. Findings: Girls categorized as non-heterosexual with nonconforming gender expression, girls categorized as non-heterosexual with neutral gender expression, and boys categorized as non-heterosexual with nonconforming gender expression reported the highest prevalence of suicidal ideation and suicide attempts. The total variance in suicidal ideation and suicide attempts attributable to the identities/positions were 12.60% and 10.50%, respectively. However, there were no significant interactive intersectional effects. Interpretation: Adolescents with multiple marginalized identities/positions showed the highest prevalence of suicidal ideation and suicide attempts. Comprehensive suicide prevention strategies should go beyond individual-level risk factors and promote holistic systemic changes. Intervention solely targeting one identity/position may not be sufficient. Funding: The data used in this study is made available by Family Planning Association of Hong Kong and the Research Subcommittee for the Youth Sexuality Study 2021. The work was supported by the Department of Health of the Hong Kong SAR Government.